2018
DOI: 10.1038/s41419-018-0905-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukaemia cells require the bone morphogenic protein pathway for cell cycle progression and self-renewal

Abstract: Leukaemic stem cell (LSC) persistence remains a major obstacle to curing chronic myeloid leukaemia (CML). The bone morphogenic protein (BMP) pathway is deregulated in CML, with altered expression and response to the BMP ligands shown to impact on LSC expansion and behaviour. In this study, we determined whether alterations in the BMP pathway gene signature had any predictive value for therapeutic response by profiling 60 CML samples at diagnosis from the UK SPIRIT2 trial and correlating the data to treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Laperrousaz et al revealed deregulation of BMPR1B/ALK6 and downstream signalling elements, such as SMAD1, SMAD4, SMAD5, SMAD6, ID2 and RUNX1 in CP CML patients compared to healthy controls [103] . Deregulation of the pathway was also confirmed by Toofan et al who showed that differential expression of BMP pathway genes such as ACV1C, INHBA, SMAD7, SNAIL1 and SMURF2 could be linked to treatment response [105] . BMPR1B/ALK6 was identified as the main driver for myeloid progenitor expansion with BCR-ABL1 oncogene being sufficient to increase BMPR1B/ALK6 cell membrane expression in CML [103] .…”
Section: Role Of the Bmp Pathway In Sustaining CML Lsc In The Bm Nichementioning
confidence: 62%
See 3 more Smart Citations
“…Laperrousaz et al revealed deregulation of BMPR1B/ALK6 and downstream signalling elements, such as SMAD1, SMAD4, SMAD5, SMAD6, ID2 and RUNX1 in CP CML patients compared to healthy controls [103] . Deregulation of the pathway was also confirmed by Toofan et al who showed that differential expression of BMP pathway genes such as ACV1C, INHBA, SMAD7, SNAIL1 and SMURF2 could be linked to treatment response [105] . BMPR1B/ALK6 was identified as the main driver for myeloid progenitor expansion with BCR-ABL1 oncogene being sufficient to increase BMPR1B/ALK6 cell membrane expression in CML [103] .…”
Section: Role Of the Bmp Pathway In Sustaining CML Lsc In The Bm Nichementioning
confidence: 62%
“…Our results showed that dual targeting of BMP pathway signalling and BCR-ABL1 leads to altered cell cycle gene transcription, irreversible cell cycle arrest, along with increased apoptosis compared to single treatments. More importantly, inhibition resulted in fewer cell divisions, reduced numbers of CD34 + cells and colony formation from CML patient samples compared with healthy controls [105] . These promising results suggest that this approach warrants further investigations.…”
Section: Targeting the Bmp Pathwaymentioning
confidence: 95%
See 2 more Smart Citations
“…The generation of immunosuppressive/tolerogenic DCs and M2 MØs has been proposed to be induced by different tumour-mediated mechanisms such as hypoxia, endoplasmic reticulum stress, and mainly exposition to several tumour-derived cytokines and growth factors [6,8,13,48]. In this context, the components of the TGF-β superfamily, including the BMPs, have been extensively reported to participate in multiple aspects of tumour biology including immune evasion [21,49,50,51] but the relevance of BMP pathway in the origin and progression of leukaemias and lymphomas is now beginning to be uncovered [24,52]. Our present data show that Nalm-6 ALL cells mainly secrete BMP4, but not other BMP ligands previously reported to be involved in lymphoid malignancies [24,53].…”
Section: Discussionmentioning
confidence: 99%